Lactobacilli regulate Staphylococcus aureus 161:2-induced pro-inflammatory T-cell responses in vitro. - Yeneneh Haileselassie; Maria A Johansson; Christine L Zimmer; Sophia Björkander; Dagbjort H Petursdottir; Johan Dicksved; Mikael Petersson; Jan-Olov Persson; Carmen Fernandez; Stefan Roos; Ulrika Holmlund; Eva Sverremark-Ekström (PLoS ONE, 2013)
There seems to be a correlation between early gut microbiota composition and postnatal immune development. Alteration in the microbial composition early in life has been associated with immune mediated diseases, such as autoimmunity and allergy. We have previously observed associations between the presence of lactobacilli and Staphylococcus (S.) aureus in the early-life gut microbiota, cytokine responses and allergy development in children. Consistent with the objective to understand how bacteria modulate the cytokine response of intestinal epithelial cell (IEC) lines and immune cells, we exposed IEC lines (HT29, SW480) to UV-killed bacteria and/or culture supernatants (-sn) from seven Lactobacillus strains and three S. aureus strains, while peripheral blood mononuclear cells (PBMC) and cord blood mononuclear cells (CBMC) from healthy donors were stimulated by bacteria-sn or with bacteria conditioned IEC-sn. Although the overall IEC response to bacterial exposure was characterized by limited sets of cytokine and chemokine production, S. aureus 161:2-sn induced an inflammatory response in the IEC, characterized by CXCL1/GROα and CXCL8/IL-8 production, partly in a MyD88-dependent manner. UV-killed bacteria did not induce a response in the IEC line, and a combination of both UV-killed bacteria and the bacteria-sn had no additive effect to that of the supernatant alone. In PBMC, most of the Lactobacillus-sn and S. aureus-sn strains were able to induce a wide array of cytokines, but only S. aureus-sn induced the T-cell associated cytokines IL-2, IL-17 and IFN-γ, independently of IEC-produced factors, and induced up regulation of CTLA-4 expression and IL-10 production by T-regulatory cells. Notably, S. aureus-sn-induced T-cell production of IFN- γ and IL-17 was down regulated by the simultaneous presence of any of the different Lactobacillus strains, while the IEC CXCL8/IL-8 response was unaltered. Thus these studies present a possible role for lactobacilli in induction of immune cell regulation, although the mechanisms need to be further elucidated.